2006
DOI: 10.1073/pnas.0609163103
|View full text |Cite
|
Sign up to set email alerts
|

Unliganded and hormone-bound glucocorticoid receptors interact with distinct hydrophobic sites in the Hsp90 C-terminal domain

Abstract: Unlike most chaperones, heat-shock protein 90 (Hsp90) interacts with a select group of ''client proteins'' that regulate essential biological processes. Little is known about how Hsp90 recognizes and binds these proteins. The glucocorticoid receptor (GR) is a well characterized Hsp90 client protein, whose hormone binding, nuclear-cytoplasmic trafficking, and transcriptional activity are regulated by Hsp90. Here, we provide evidence that unliganded and hormone-bound GR interact with two distinct, solventexposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 42 publications
1
61
0
Order By: Relevance
“…These helices, which show conformational heterogeneity in crystal structures, possibly make contacts that link the interface rearrangements on opposite monomers. Since these helices make important contacts in the proposed interaction site of the glucocorticoid receptor, 33 this speculation suggests a coupling between substrate binding and Hsp90 conformation. Indeed, the closed state of HtpG has been shown to increase anti-aggregation activity for the citrate synthase model substrate.…”
Section: Discussionmentioning
confidence: 99%
“…These helices, which show conformational heterogeneity in crystal structures, possibly make contacts that link the interface rearrangements on opposite monomers. Since these helices make important contacts in the proposed interaction site of the glucocorticoid receptor, 33 this speculation suggests a coupling between substrate binding and Hsp90 conformation. Indeed, the closed state of HtpG has been shown to increase anti-aggregation activity for the citrate synthase model substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies by Darimont and coworkers have confirmed that Hsp90 helix 2 stabilizes unliganded GR by engaging apo-GR at the position normally occupied by receptor helix 12 in response to hormonal activation and forcing the flexible helix 12 to bind to the hydrophobic groove, at the same time preventing receptor interaction with coactivators (Fang et al, 2006). The resulting structure corresponds to the native conformation of unliganded GR, with an orientation of helix 12 similar to that in antagonist (RU486)-bound GR (Fang et al, 2006;Kauppi et al, 2003).…”
Section: Flexible Positioning Of Receptor Lbd Helix 12; Hsp90 Helix 2mentioning
confidence: 90%
“…The resulting structure corresponds to the native conformation of unliganded GR, with an orientation of helix 12 similar to that in antagonist (RU486)-bound GR (Fang et al, 2006;Kauppi et al, 2003). On agonist binding, hormone-induced conformational changes within the LBD of holo-GR promote the replacement of Hsp90 helix 2 by receptor helix 12, causing loss of Hsp90 chaperone machinery and establishing the AF2 contact domain for coactivator interaction.…”
Section: Flexible Positioning Of Receptor Lbd Helix 12; Hsp90 Helix 2mentioning
confidence: 99%
See 1 more Smart Citation
“…Ricketson and co-workers were able to demonstrate, through amino acid substitution, that this surface is required for HSP90 interaction (Ricketson et al, 2007). HSP90 recognises the GR LBD through two, defined hydrophobic sites and binds to a solvent accessible major groove maintaining GR stability and permitting highaffinity ligand binding (Fang et al, 2006), as depicted in Fig. 7G.…”
Section: Discussionmentioning
confidence: 99%